Digital Disclosure of Delinquency: Online Peers and the Sharing of Offline Crime - McCuddy, Timothy (Crime & delinquency, 2022)
Digital communication poses challenges for scholars interested in the link between peers and crime since youth are often less inhibited online and can more easily share their opinions and experiences with offline activities. Drawing on longitudinal data from middle and high school students, this study explores how online communication impacts the sharing of personal and peer delinquency. Criminogenic risk factors are largely unrelated to the digital disclosure of personal delinquency among those who offend; however, peer online disclosure is related to self-reported delinquency, independent of perceived peer delinquency. These findings suggest cyberspace may extend offline mechanisms of peer influence beyond providing a unique source of online influence.